Impact of the PROFHER trial findings on surgeons' clinical practice: An online questionnaire survey. Issue 10 (October 2017) - Jefferson, L.; Brealey, S.; Handoll, H.; Keding, A.; Kottam, L.; Sbizzera, I.; Rangan, A.
Abstract : Objectives: To explore whether orthopaedic surgeons have adopted the Proximal Fracture of the Humerus: Evaluation by Randomisation (PROFHER) trial results routinely into clinical practice. Methods: A questionnaire was piloted with six orthopaedic surgeons using a 'think aloud' process. The final questionnaire contained 29 items and was distributed online to surgeon members of the British Orthopaedic Association and British Elbow and Shoulder Society. Descriptive statistics summarised the sample characteristics and fracture treatment of respondents overall, and grouped them by whether they changed practice based on PROFHER trial findings. Free-text responses were analysed qualitatively for emerging themes using Framework Analysis principles. Results: There were complete responses from 265 orthopaedic and trauma surgeons who treat patients with proximal humeral fractures. Around half (137) had changed practice to various extents because of PROFHER, by operating on fewer PROFHER-eligible fractures. A third (43) of the 128 respondents who had not changed practice were already managing patients non-operatively. Those who changed practice were more likely to be younger, work in a trauma unit rather than a major trauma centre, be specialist shoulder surgeons and treat fewer PROFHER-eligible fractures surgically. This group gave higher scores when assessing validity and applicability of PROFHER. In contrast, a quarter of the non-changers were critical, sometimes emphatically, of PROFHER. The strongest theme that emerged overall was the endorsement of evidence-based practice. Conclusion: PROFHER has had an impact on surgeons' clinical practice, both through changing it, and through underpinning existing non-operative practice. Although some respondents expressed reservations about the trial, evidence from such trials was found to be the most important influence on surgeons' decisions to change practice. Cite this article : L. Jefferson, S. Brealey, H. Handoll, A. Keding, L. Kottam, I. Sbizzera, A. Rangan. Impact of the PROFHER trial findings on surgeons' clinical practice: An online questionnaire survey. Bone Joint Res 2017;6:590–599. DOI: 10.1302/2046-3758.610.BJR-2017-0170.